STUDY ON THE APPLICATION OF "INCLUSIVE ARCHITECTURE" IN CREATIVE CENTER BUILDINGS IN MALANG - Damardjelang Ramadhan; Eva Elviana (DEARSIP : Journal of Architecture and Civil, 2025)
The development of the creative economy sector in Indonesia encourages the presence of public facilities in the form of Creative Centers as a space for collaboration, production, and development of creative communities. However, questions arise whether the facility has been truly inclusive and able to accommodate all groups of people, including people with disabilities. This study aims to examine the application of inclusive architecture in the Malang Creative Center (MCC) building through a descriptive-qualitative approach. Data were obtained through field observation on the exterior and interior areas of buildings, as well as literature studies related to the principles of Universal Design and accessibility standards of the Minister of PUPR No.14/2017. The results of the study show that the application of the principle of inclusivity in MCC is in the category of being quite appropriate. Facilities such as elevators and disabled toilets have met some Universal Design principles, but important elements such as guiding blocks, contrast signage, braille handrails, and pedestrian connectivity to buildings have not been met. Based on the conformity evaluation, as many as 4 components were classified as partially compliant, 4 components were not compliant, and only 1 component was considered compliant. These findings are expected to be considered for the development of Creative Center facilities that are more inclusive, safe, and friendly for all users.